Integration Method for Response History Analysis of Single-Degree-of-Freedom Systems with Negative Stiffness - Nikoleta Chatzikonstantinou; Triantafyllos K. Makarios; Asimina Athanatopoulou (Buildings, 2022)
The present article deals with the mathematical investigation of a negative-stiffness ideal system that can be used in seismic isolation of civil engineering structures. Negative-stiffness systems can be used in the seismic isolation of structures, because in the case of a strong earthquake, they do not easily allow vibrations to develop. These negative-stiffness systems can be significantly more efficient than the usual seismic isolation systems, as they drastically reduce the vibrational amplitudes of structures, as well as eliminate the inertial seismic structure loadings. The mathematical investigation of a negative-stiffness ideal system provides documented answers about the effect of negative-stiffness systems in the seismic behavior of structures. First, the differential equation of motion of a single-degree-of-freedom oscillator (SDoF) is formulated, without classical damping, but with negative stiffness. Furthermore, the mathematical solution of the equation of motion is given, where it is proven that this solution does not describe a structure vibration. Furthermore, the seismic structure motion follows an exponential increase when the seismic ground excitation is purely sinusoidal. Finally, to calculate the real response of the negative-stiffness system, a suitable modification of the Newmark iterative numerical method is proposed.